Biochar Rice Husk Charcoal on Growth and Production of Long Bean Plants (Vigna sinensis L.): Formulation Analysis - Arviana Walianggen (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Rice husk charcoal has an important role as a soil-improving material, especially in improving soil physical properties such as porosity, aerase and drainage so as to make it easier for roots to develop and absorb nutrients. This study aims toincrease the growth and production of long bean crops by providing biochar charcoal husks and improving land productivity in sustainable agricultural enterprises. This study used a Randomized Group Design (RAK) with one factor consisting of 5 treatments and 3 groups. The treatment in this study was B0 = 0 tons / ha, B1 = 2.5 tons / ha, B2 = 5 tons / ha, B3 = 7.5 tons / ha and B4 = 10 tons / ha. The results showed that giving several doses of biochar charcoal husks to rice was able to increase the growth and yield of long bean plants. The provision of rice husk charcoal biochar has a noticeable influence on the parameters of plant height, fresh weight of plants and fruit weight of long bean plants per plot. The results of the study wereobtained in the B3 treatment, namely the administration of rice husk charcoal biochar at a dose of 7.5 tons / ha for the parameters of plant height, fresh weight of long bean plants and fruit weight per plot